Influence of Temperatures on the Tautomerism of the N-(1H-imidazoline-2-yl)-1H-benzimidazol-2-amine and Investigation of Its Electrochemical Behaviour - Servi, Suleyman; Genc, Murat; Saydam, Sinan (Wiley-V C H Verlag Gmbh, 2012)
Synthesis of N-(1H-imidazoline-2-yl)-1H-benzimidazol-2-amine was carried out under microwave irradiation (MWI) conditions. Dynamic 1H NMR investigation of N-(1H-imidazoline-2-yl)-1H-benzimidazol-2-amine compound was reported at temperature range of 223333 K in DMF-d7. Some physical parameters, such as coalescence temperature (Tc), the free energy of activation (?G*?) and rate constant (k) values were calculated from its 1H NMR spectra at various temperatures. Electrochemical feature of this compound was investigated by cyclic (CV) and square wave voltammetry (SWV).
Keywords: benzimidazole; tautomerism; dynamic NMR; cyclic voltammetry